Individuation, Orphans, and Case? - Franks, Steven; Peti-Stantić, Anita (2010)
The presentation shed some new light to old questions about the so called Orphan Accusative in Slovenian. These questions are, following Perlmutter and Orešnik (1973): 1. Why is it that the special form found in the OA is not just and arbitrary ending? 2. Why is the OA form the same as that of the genitive case? 3. Why do all constituents with adjectival endings, rather than just quantifiers or demonstratives or just adjectives that refer to transient properties, have a special form for the OA? 4. Why is it that masculines have a special OA form and feminines do not? 5. Why is it that the accusative has a special form, rather than some other case? 6. Why is there a special form in the absence of the head noun, and not some other environment? 7. Why Slovenian - what is particular to Slvn in the OA phenomenon, and what is more general? Our questions, echoing P and O, were: 1. How does the OA work? 2. Why is the form of the orphaned adjective(s) genitive(-like)? 3. Why does this happen in Slvn but not in other Slavic languages?
Projekt MZOS
ENG